Poultry Revolution in India: Lessons for smallholder production systems - Ashok Gulati; Ritika Juneja (University of Bonn, Center for Development Research (ZEF), 2023)
Poultry has been the fastest growing sector of Indian agriculture over the last two decades. Between 2000 and 2020, India's poultry meat and egg production grew at an annual average rate of growth of 9.2 percent and 7.2 percent, respectively. For comparison, cereal production grew just 1.5 percent over the same period. This is nothing short of a revolutionary change in India's poultry sector. In fact, this is even higher than the rate of growth achieved in wheat production (8.4 percent per annum) and rice (5 percent per annum) during the heydays of the Green Revolution (1967-1986) and the White Revolution in milk (1970-1997) which saw growth of 4.5 percent. Yet, this poultry revolution has not been as well studied and is not as well-known as the Green and White Revolutions have been. This paper makes a modest attempt in this direction with a view to uncover the sector's key drivers and explore whether there are any lessons to be learned for smallholder economies around the developing world. Our research on India's poultry sector reveals that as a result of this fast increase in poultry production, India is now the third largest producer of eggs in the world (producing 122 billion eggs in 2020-2021) after China and the USA, and the fifth largest producer of broilers (producing 4.4 million metric tonnes (MMT) in 2020-2021) after China, the USA, Brazil and the Russian Federation. Two factors acted as catalysts of change: (1) the government policy of liberalizing imports of grandparent poultry stock; and (2) the emergence of a vertical integration model between large integrators/hatcheries and small farmers through a contract farming approach, purely driven by the private sector. It is this "double engine" of policy change by the government and institutional innovation of large integrators linking with small farmers that transformed the Indian poultry sector from a mere backyard activity into a major organized commercial one. In 2020, almost 80 percent of India's poultry production (in value terms) came from this organized contract farming segment, far more than any other commodity in Indian agriculture. In this study, we also explore the inclusivity of the contract farming model with large integrators. Interestingly, we find that almost 70 percent of poultry farmers engaged through contract farming are smallholders with a flock size of 3,000-10,000 birds; 20 percent are medium scale farmers with 10,000- 50,000 birds, and only 10 percent are large scale farmers with 50,000-400,000 birds. This reality has a number of lessons for many smallholder economies of the developing world, where they can find opportunities for augmenting incomes of smallholders by linking with large integrators who have the capacity to infuse credit and insurance while bearing market risksin the poultry value chain. This allows smallholders to have dependable and regular income at equal intervals. Being a good source of protein, poultry can potentially also help improve the nutrition status of all Indians with some education and awareness about the nutritional value of eggs and poultry meat. However, despite this remarkable growth in poultry production, the sector also faces many challenges. The retailing of poultry meat is largely a wet market phenomenon in the informal sector, raising concerns about hygiene and food safety. Also, the infrastructure for freezing poultry meat all along the value chain is negligible and often absent. This limits India's participation in global trade of poultry meat. Occasional outbreaks of avian flu add to these challenges. India still has low levels of per capita consumption of poultry meat, partly because of relatively low levels of incomes of the masses and partly due to a "vegetarian" culture in some pockets of the country. Nevertheless, the potential for poultry seems large in the years to come as India's per capita incomes rise. However, the environmental footprint of rapidly increasing poultry farms, such as waste generated from slaughtering, rendering material from processing units, improper management of litter and excreta of the birds, needs to be tackled in a manner that ensures sustainable growth of this sector. This would be done as better infrastructure is built, and food safety, environment and animal welfare concerns get their due attention. We conclude that this institutional innovation of integrating large hatcheries with thousands of small poultry farmers, a unique hallmark of this sector, could pave the path towards shared prosperity and better nutrition for all.
Keywords: 330